1999
DOI: 10.1159/000030420
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Carcinoma of the Prostate

Abstract: Prognostic factors for prostatic carcinoma should be significant, independent and clinically important. They should be of practical use, and their determination should be affordable in everday practice. Prognostic factors may be grouped into patient-related, tumor-related and treatment-related. They should meet certain requirements, such as possession of a clear biological significance, an adequate sample size (possibly more than 150 patients), no patient population bias, an adequate statistical test, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Analysis of prostate-specific gene expression in TRAMP C-1 cell line showed that non-stimulated TRAMP C-1 cells express prostate specific antigens such as prostate stem-cell antigen (PSCA), prostatespecific membrane antigen (PSMA), and prostatic acid phosphatase (PAP) [20]. Elevated expression of these antigens in human tumors correlates with increased tumor stage, grade, and progression to androgen independence [21][22][23]. It has been postulated that prostate-specific antigens may be processed by the prostatic epithelial cells with tumor generating fragments through MHC I molecules, therefore these proteins may serve as T cell epitopes allowing to identify and eliminate prostate cancer [20].…”
mentioning
confidence: 99%
“…Analysis of prostate-specific gene expression in TRAMP C-1 cell line showed that non-stimulated TRAMP C-1 cells express prostate specific antigens such as prostate stem-cell antigen (PSCA), prostatespecific membrane antigen (PSMA), and prostatic acid phosphatase (PAP) [20]. Elevated expression of these antigens in human tumors correlates with increased tumor stage, grade, and progression to androgen independence [21][22][23]. It has been postulated that prostate-specific antigens may be processed by the prostatic epithelial cells with tumor generating fragments through MHC I molecules, therefore these proteins may serve as T cell epitopes allowing to identify and eliminate prostate cancer [20].…”
mentioning
confidence: 99%